PT e social-democracia: analisando a trajetória e os governos petistas - Beker, Matheus Haruo (2020)
This research aims to answer the following question: does the Workers Party act as a social democratic party? The objective is to assess whether the party had social democratic characteristics in its party trajectory and in the policies implemented while it was in the federal government. To contemplate this objective, we will employ the study of social democracy characteristics and the trajectory of its parties relating these aspects to the PT trajectory and its actions in front of the executive. Our analysis concludes that the purpose and the way in which the PT ruled, along with the analysis of PT's trajectory, indicate that the party has sufficiently social-democratic elements, although not fully satisfying the social-democratic ideal type. A secondary objective is to discuss the methodology regarding the study of social democratic parties, mobilizing different elements from that used by traditional literature and making notes on a different methodology. Studying and understanding the ideology that guided the PT during the government is of great value to political science since the party has constituted itself as the main left force in Brazil in recent decades, thus the expected contribution is to assist future studies in understanding the Brazilian political system and the strategies employed by PT in the past, present and future.